Spinor Darboux equations of curves in Euclidean 3-space - Kisi Ilim; Tosun Murat (Mathematica Moravica)
In this paper, the spinor formulation of Darboux frame on an oriented surface is given. Also, the relation between spinor formulation of Frenet frame and Darboux frame is obtained.